Molecular Biomarkers for Prenatal Diagnosis of Beta-Thalassemia at Hyderabad Sindh - Sumera Abbasi, Vershia Kanwal, Benazeer Bhatti, Muhammad Sarwar Khan, Kiran Memon, Raima Kalhoro, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Thalassemia Is Disease Which Is Due To Defect In Hemoglobin Synthesis Resulting In Severe Anemia. The thalassemia disorder is genetic syndrome resulting from absence or markedly reduced production of one of the globin subunits of hemoglobin. In alpha (α)-thalassemia, production of alpha – subunit of globin is absent or decreased, while in the beta (β)-thalassemia, production of β – globin subunit is absent or reduced. Aim: To find common mutations inside beta globin gene. To find new polymorphism inside beta-globin gene will help in future as part of prenatal diagnosis. Methods: This study includes all cases of beta thalassemia minor diagnosed by normal prenatal testing while the mother's hemoglobin concentration is less than 27 pg and her total cell volume is less than 76 fl. Two EDTA tubes were filled with eight milliliters of blood after patients' samples were taken. ARMS PCR required 5 milliliters of EDTA sample, whereas HB electrophoresis and complete blood count (CBC) required 3 milliliters of EDTA tube. We used SPSS version 21 to evaluate all the data that was recorded using a self-made proforma. Results: For the cases, the mean age was determined to be 26.83, whereas for the controls, it was 27.05.While the majority of patients had a history of thalassemia in their families (74%; 54/73), 27.4% (20/73) of the subjects did not have a consanguineous marriage, and 26.0% (19/73) did not have a thalassemia in their family history. The average hemoglobin (HB) level in the control group was 12.32 g/dl, but in the patients it was 10.10. The case group also had significantly lower MCV and MCH values than the control group. ARMS PCR revealed the following mutation frequencies: IVS-1-5 (42.5%) in 31 cases, Fr 8/9 (27%) in 20 cases, IVS-1-1 (11%) in 08 cases, Del 619 (5.5%) in 4 cases, CD-30 (5.5%) in 4 cases, CD-5 (5.5%) in 4 cases, and Fr 41/42 (3%), in two cases of selected Beta patients, as the fifth most common mutation. Conclusion: Among the mutations detected in Hyderabad and the surrounding areas, the most common ones in beta thalassemia were IVS1-5 and Fr 8/9. Other variants were IVS1-1, Del-619, CD-30, CD-15, and fr 41/42. A sensitive molecular diagnostic and screening test for thalassemia can be used in our community with the ARMS PCR assay. Keywords: ARMS PCR, Beta Thalassemia, Mutations